Clinical pathology resident education during the COVID-19 pandemic. Issue 3 (14th December 2020) - Senzel, Lisa; Ahmed, Tahmeena; Batiste, Rebecca
Abstract : COVID-19 arrived at our medical centre in March 2020 with substantial force. Clinical pathology concepts began to have a new, direct relevance to our residents' lives. As we wondered 'Have I been exposed? Do I need to self-isolate? Are the tests reliable? Am I protecting myself adequately while handling specimens?', these questions drew new interest in laboratory methods, test interpretation and limitations, supply chain issues, safety and quality. By incorporating SARS-CoV-2 teaching points into laboratory medicine lectures, we enlivened concepts of sensitivity, specificity, predictive value and methodologic issues in serologic, molecular and antigen testing for pathology residents. We drew from the emerging literature on SARS-CoV-2 to create lectures and added details from our own institutional experience with COVID-19. When the pandemic fades from memory, clinical pathology education can still benefit from mnemonics, analogies, anecdotes and creative efforts that capture the attention of the audience.